PENGARUH OBESITAS TERHADAP KEJADIAN HIPERTENSI DALAM MASA KEHAMILAN DI PUSKESMAS HARAPAN RAYA PEKANBARU - isnaniar, isnaniar; Norlita, Wiwik; Safitri, Niken (Sistem Informasi, 2019)
OBESITY INFLUENCE ON HYPERTENSION IN PREGNANCY IN PUSKESMAS HARAPAN RAYA PEKANBARU  Isnaniar, Wiwik Norlita, Niken Safitri  Nursing Diploma III Study Program at Muhammadiyah University of Riau e-mail: isnaniar@umri.ac.id, wiwiknorlita@umri.ac.id,nikensafitri@studentumri.ac.id   ABSTRACT  Background: Pregnancy of obese mothers has a strong role in the occurrence of an increase in blood pressure on the examination of pregnant women. Currently obesity gets serious attention because the increasing number of sufferers including women in reproductive age and the number of obese people in pregnant women also increased by around 18.5% to 38.3%. Based on the Preliminary Survey conducted by researchers on July 2, 2018 In 10 respondents pregnant women obtained data that pregnant women who have a history of hypertension during pregnancy 2 people (20%) who are obese 4 people (40%), and who have hypertension 4 people (40%) Purpose: This study was to determine the effect of obesity on hypertension in Harapan Raya Pekanbaru Health Center.  Method: The design of this study is a Cross Sectional study, this design is a research design whose measurement or observation is done simultaneously at a time (once). The subjects in this study were 35 pregnant women collecting data using questionnaires and observations. Statistical tests using the chi square correlation test. Results: Most obese pregnant women were 34.3% (12 respondents) and pregnant women who had hypertension 7 (54.55%) and based on statistics showed the results of the chi square test with significance level (α) were ≤ 0.05 Probability value (p) is 0.013. Conclusion: It is expected that pregnant women in the category of obesity can further reduce the factors that cause obesity during the period before pregnancy and during pregnancy. So that pregnant women can control their bodies during their pregnancy and not become a category of obesity that can cause hypertension in the mother.  Keywords: Obesity Pregnant Women, Hypertension